PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS WORDWALL UNTUK PENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PKN - Emah, Emah (UNTIRTA CIVIC EDUCATION JOURNAL, 2022)
This research is based on the fact that students tend to be unmotivated to learn, seem bored and passive in the learning process. The purpose of this study is to determine the effect of using wordwall-based learning media in increasing students' interest in learning PKn subjects at MTS Ar-ridho Waringinkurung. The method used is The type of research used in this study is an experimental research method, with a population of all students of MTS Ar-ridho Waringinkurung and a sample of 28 students. Data collection techniques using observation, questionnaires, documentation. Data analysis was carried out at the beginning of learning (pre-test) and after learning (post-test), where the average value for the pre-test was 59.93 for the experimental class and 53.64 for the control class, for the post-test results the average value for the experimental class was 62.71 and the control class 57.14. To find out the increase in learning interest, a normality test was conducted for the pre-test with a sig value of 0.191 for the experimental class and 0.143 for the control class, for the post-test results with a sig value of 0.706 for the experimental class and 0.3241 for the control class. The homogeneity test for the pre-test had a sig value of 0.120 and for the post-test sig 0.214 t-test where it had sig <0.001 for the pre-test and sig <0.001 for the post-test where both data were <0.005, it can be concluded that there is a difference and an increase in wordwall-based learning on the interest in learning Civics in the experimental class compared to the control class.